Investor Protection in Times of Crisis of Financial Institutions in Spain in Light of EU Regulations - Kozłowska, Maja (University of Wroclaw. Faculty of Law, Administration & Economics, 2016)
The objective of this paper is to explore selected strategies of countering the financial crisis in Spain, with a special focus on the issue of investor protection. I will attempt to highlight good solutions and the most significant mistakes made in the struggle to tackle the crisis, based on comments provided by experts in the field - both scholars and practitioners. Owing to the great complexity of the subject, in this work I focus on aspects connected with the restructuring of Spanish banking institutions and with the deposit guarantee system, and I discuss the efforts to overcome the financial crisis in Spain within the context of new challenges to public law (especially in light of the new European supervision system).The objective of this paper is to explore selected strategies of countering the financial crisis in Spain, with a special focus on the issue of investor protection. I will attempt to highlight good solutions and the most significant mistakes made in the struggle to tackle the crisis, based on comments provided by experts in the field - both scholars and practitioners. Owing to the great complexity of the subject, in this work I focus on aspects connected with the restructuring of Spanish banking institutions and with the deposit guarantee system, and I discuss the efforts to overcome the financial crisis in Spain within the context of new challenges to public law (especially in light of the new European supervision system).
Keywords: kryzys finansowy; ochrona inwestorów; instytucje bankowe